1991
DOI: 10.1007/bf02238525
|View full text |Cite
|
Sign up to set email alerts
|

Open heart surgery in children of Jehovah's witnesses: Extreme hemodilution on cardiopulmonary bypass

Abstract: Between January 1979 and July 1989, 15 children of Jehovah's Witnesses underwent corrective open surgery for congenital heart disease (CHD) on cardiopulmonary bypass (CPB). Ages ranged from 1.5-17 years and body weight from 9.1-63 kg, with five patients weighing less than 15 kg. Eight children were cyanotic, and two of them had had previous thoracic operations. All operations were performed in moderate to deep hypothermia using a modified version of isovolemic hemodilution with bloodless priming technique of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Experience with children of members of the Jehovah Witness faith in two centres did not report any increase in the incidence of postoperative neurological deficits. 6s, 69 Henling et al 68 reviewed the perioperative courses of 110 children of members of the Jehovah Witness faith who underwent cardiac surgery during normothermic cardiopulmonary bypass with a glucose cl3rstalloid prime. These children ranged in age from six months to 12 yr mad weighed 5.2 to 42.3 kg.…”
Section: Haemodilutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience with children of members of the Jehovah Witness faith in two centres did not report any increase in the incidence of postoperative neurological deficits. 6s, 69 Henling et al 68 reviewed the perioperative courses of 110 children of members of the Jehovah Witness faith who underwent cardiac surgery during normothermic cardiopulmonary bypass with a glucose cl3rstalloid prime. These children ranged in age from six months to 12 yr mad weighed 5.2 to 42.3 kg.…”
Section: Haemodilutionmentioning
confidence: 99%
“…Stein et al 69 reported the use of a modified version of isovolaemic haemodilution and a bloodless prime technique during moderate to profound hypothermic CPB or total circulatory arrest in 15 children of Jehovah Witnesses, aged between 1.5 and 17 yr. Mean haematocrit levels achieved during bypass was 17.9%.…”
Section: Haemodilutionmentioning
confidence: 99%
“…1 The endovascular treatment of aortic disease has emerged as an alternative for patients with severe comorbid disease, who are not good candidates for open surgery. [6][7][8] Acute type-B aortic dissection is usually treated medically with vasodilators and -blockers; however, aneurysmal dilatation of the dissected aorta eventually occurs in 14%-20% of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The religious belief of Jehovah's Witnesses, based on their interpretation of the Bible (Genesis 9:3-6, Leviticus 17:10, and Acts 15:28,29), forbids the transfusion of homologous blood products. 1 The surgical treatment of cardiac disease in this population is well documented worldwide, 2-5 but there is still limited clinical experience in treating Jehovah's Witnesses with thoracic aneurysms. 4,5 Thoracic aortic aneurysm repair often requires the transfusion of large quantities of blood products; however, blood conservation tech- artery.…”
Section: Introductionmentioning
confidence: 99%
“…There was one death related to persistent pulmonary hypertension (27). To revert hemodilution after CPB, modified ultrafiltration has been used (28,29).…”
Section: Introductionmentioning
confidence: 99%